Will It Be Deja Vu All Over Again? - J.C. Herbert Emery; Ronald D. Kneebone (The School of Public Policy Publications, 2009)
The boom and bust in energy prices experienced recently has its parallels in the boom and bust of energy prices in the 1970s and 1980s. The earlier boom period saw the Government of Alberta struggle with restraining spending and so became heavily dependent on high energy prices. When in 1986 energy prices crashed the government suﬀ ered a string of large deﬁ cits that was followed by draconian cuts to spending. From 2000 to 2008 the government enjoyed another boom in energy prices and again found it diﬃ cult to restrain spending. The recent crash in energy prices threatens the government with repea ng the earlier experience of deﬁ cits followed by drama c spending cuts. As it prepares its 2009 budget the government has an opportunity to learn from the past and to quickly and decisively put its budget on a path toward a much smaller reliance on energy-related revenues.